Identificação de Coesão Social em AVEAs - Bastos, Helvia P. P.; Bercht, Magda; Wives, Leandro Krug; Martins, Yasmmin C. (Cadernos de Informática, 2011)
The study presents a lexicometric analysis of terms of sociability in educational chats. We designated three lexical classes as indicators of social cohesion following the model given by Rourke et al. for assessment of social presence in discursive interactions on line. Data obtained in the processing of occurrences show the viability of identifying the variation of social cohesion expressions, and its possible use as a tool for diagnosing student participation in virtual learning environments. Key words: Lexicometry, Social Presence, Cohesion, Chats.